Diiodine–Triethylsilane System: A Practical Method for Deprotection of Aryl Benzyl Ethers - Jiang, Jin; Wang, Zhuo (Synlett, 2024)
A practical method for the debenzylation of aryl benzyl ethers has been developed using easy-to-operate I2 and Et3SiH, as well as the green solvent ethyl acetate. Halo, methoxy, ester, and nitro groups on the benzene ring of the aryl benzyl ether are compatible with this debenzylation. Control experiments revealed that Et3SiI, generated in situ, might be the actual promoter of the procedure. This method does not require a separate desilylation reaction to obtain phenol products.
Keywords: deprotection; debenzylation; iodine; triethylsilane; ethers